Variasi Leksikal Bahasa Musi di Sungsang - Muchti, Andina; Selvia, Delvi (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to describe the lexical variations of the Musi language in Sungsang. This lexical variation can be demonstrated by looking for similarities and differences in Musi language variations in Sungsang. The method used is a qualitative description. Data collection techniques using observation, interviews, recording, and recording techniques. Data analysis techniques data checking with data reduction, data transcription, data classification, data interpretation, and conclusions. The results showed that: 1) Swades basic vocabulary there are 20 different words and 20 similarity words, 2) body parts there are 5 differences and 6 similarities, 3) greeting pronouns there are 4 different words and 2 similarity words 4) kinship system there are 3 words differences and 2 words of equality, 5) village and community life there are 7 words of difference and 4 words of equality, 6) house and parts there are 7 words of difference and 5 words of equality, 7) equipment and supplies there are 10 words of difference and 6 words of similarity, 8) food and drinks there are 5 words of difference and 2 words of equality, 9) seasons, natural conditions, natural objects, and directions there are 14 words of difference and 9 words of equality, 10) mannerism and adjectives there are 20 words of difference and 5 words of similarity, 11) clothing and jewelry there are 6 words of difference and 8 words of equality, 12) motion and work there are 20 words of difference and 10 words of equality, and 12) animals there are 6 words of difference and 1 similarity of language Musi, ko sakata that do not experience differences in plant, yard and tree vocabulary. Musi language variations are mostly found in Sungsang I Village with 60 vocabularies, while Musi language equation is more in Sungsang III village with 162 vocabularies.